2008
DOI: 10.1517/13543784.17.10.1573
|View full text |Cite
|
Sign up to set email alerts
|

Expert opinion on tilarginine in the treatment of shock

Abstract: Tilarginine is L -N -monomethyl arginine ( L -NMMA) or N (G)-monomethyl-Larginine HCL, a non-selective inhibitor of nitric oxide synthase (NOS), which has been studied in the treatment of septic shock and cardiogenic shock complicating myocardial infarction. Despite strong evidence that excessive nitric oxide (NO) production plays a pivotal role in the pathogenesis of septic shock and may contribute to the pathogenesis of cardiogenic shock complicating myocardial infarction, outcome studies in these two disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Numerous human and experimental studies have examined the effects of NOS inhibitors, but in general the outcomes have been disappointing (9,22). A possible reason for the lack of success is that nonselective inhibitors block not only the excessive production of NO from iNOS, which is thought to be mainly detrimental, but also the ben eficial actions of NO produced by eNOS and nNOS (12,23). In septic AKI, excessive NO derived from increased iNOS activity is believed to induce systemic vasodila tation and hyperdynamic septic shock (24) and may cause deterioration of glomerular filtration and tubular func tion.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous human and experimental studies have examined the effects of NOS inhibitors, but in general the outcomes have been disappointing (9,22). A possible reason for the lack of success is that nonselective inhibitors block not only the excessive production of NO from iNOS, which is thought to be mainly detrimental, but also the ben eficial actions of NO produced by eNOS and nNOS (12,23). In septic AKI, excessive NO derived from increased iNOS activity is believed to induce systemic vasodila tation and hyperdynamic septic shock (24) and may cause deterioration of glomerular filtration and tubular func tion.…”
Section: Discussionmentioning
confidence: 99%
“…191 However, in the best-known clinical trial for cardiogenic shock in infarction patients (the TRIUMPH trial), 192 compound 2 failed to reduce severity of heart failure or mortality and also resulted in hypertension. It was hypothesized that lack of selectivity 193 or too low a dose 194 could have been responsible for these failures. A recent study (2015) using resuscitated swine found that neither global NOS inhibition (using 1) nor more selective iNOS inhibition (using 4) improves survival or myocardial dysfunction following ventricular fibrillation in cardiac arrest (when iNOS levels increase).…”
Section: Clinical Failuresmentioning
confidence: 99%
“…Therapy with L-NMMA was associated with excess mortality, particularly at doses> 5 mg/(kg h), noting that septic and cardiogenic shock in the effects of a lower dose (1 mg/(kg h)) were neutral. The excessive mortality in patients with septic shock was almost certainly the result of unfavorable hemodynamic changes induced by L-NMMA (decreased cardiac output, increased pulmonary vascular resistance and impaired tissue oxygen supply) [40][41][42].…”
Section: Nos Blockersmentioning
confidence: 99%